Gestational weight gain and its effect on fetomaternal outcome - Singh, Khushboo; Goel, Alka; Narain, Anupriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: In normal pregnancy, variable amount of weight gain is a constant phenomenon. The study aims to find an association between gestational weight gain and fetomaternal outcome. GWG (using institute of medicines guidelines meant for US population) and pregnancy outcomes among Asian Indians across different BMI categories (according to WHO Asia Pacific BMI cut points) were studied. Methods: 300 women were split into the three groups based on their gestational weight gain. Namely, below recommended GWG, recommended GWG and above recommended GWG group. Comparison of various fetomaternal outcomes was done between these groups. Results: In women, who had higher than recommended GWG, 30.5% developed GDM, 23.2% had gestational hypertensive disorder, 36.6% developed hypothyroidism, 12.2% had pre-term birth and 15.9% had low birth weight. In recommended GWG category, these were 5.4%, 4.5%, 30.6%, 7.2% and 17.1% respectively; and in below recommended category, these were 14%, 1.9%, 22.4%,12.1% and 24.3% respectively. Conclusions: GWG generally follows the BMI pattern at the time of entering into pregnancy, higher the BMI more the GWG. More GWG was associated with GDM, Gestational hypertensive disorders and poor APGAR at birth. Below recommended GWG was associated with higher occurrence of GDM. No statistical correlation, between GWG and mode of delivery, NICU stay, preterm birth and birth weight was observed. Larger study is required to establish the applicability of IOM Guidelines for GWG on Indian women.